PENGARUH E-COMMERCE TERHADAP PENINGKATAN PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH DI KOTA PADANG - HELMALIA HELMALIA; AFRINAWATI AFRINAWATI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The purpose of this study was to determine the effect of e-commerce on increasing revenue of BNI-assisted MSMEs in Padang City. The object of the research is MSMEs in Padang City, West Sumatra. The formulation of the research problem is: how is the influence of e-commerce on increasing the income of Micro, Small and Medium Enterprises in Padang City. The research hypothesis is: E-Commerce has a significant influence on increasing the income of MSMEs. The research approach is quantitative. The study population was 108 MSME units. The number of research samples was 52 MSMEs. Data collection using a questionnaire. Data analysis uses simple linear regression. The results of the study found: e-commerce has a significant effect on increasing revenue of MSMEs.